2017
DOI: 10.14814/phy2.13524
|View full text |Cite
|
Sign up to set email alerts
|

The impact of acute bouts of interval and continuous walking on energy‐intake and appetite regulation in subjects with type 2 diabetes

Abstract: In healthy subjects, it has been suggested that exercise may acutely suppress energy‐intake and appetite, with peak intensity being an important determinant for this effect. In subjects with type 2 diabetes (T2D), the effect of exercise on appetite‐related variables is, however, virtually unknown. We aimed to assess the effects of two exercise interventions, differing with regards to peak intensity, on energy‐intake, satiety and appetite‐related hormones in subjects with T2D. Thirteen subjects with T2D complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 37 publications
0
12
1
Order By: Relevance
“…Following acute endurance exercise (aerobic or high-intensity endurance exercise), either no effect or the suppression of appetite was observed for up to 180 min after the training session [ 48 , 49 ]. One of two studies that measured appetite ratings the day after exercise [ 46 , 49 ] found an increase in appetite on day 2 [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following acute endurance exercise (aerobic or high-intensity endurance exercise), either no effect or the suppression of appetite was observed for up to 180 min after the training session [ 48 , 49 ]. One of two studies that measured appetite ratings the day after exercise [ 46 , 49 ] found an increase in appetite on day 2 [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…The above-mentioned effects of endurance exercise on appetite ratings were inconsistently supported by changes in appetite hormones. Two studies observed no significant changes in the measured appetite hormones (ghrelin, PP, PYY, and leptin), although the feeling of fullness increased at certain measurement timepoints [ 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pancreatic polypeptide concentrations were also reduced immediately after exercise, but were not different to the non-exercise control condition ~20-30 minutes post-exercise. Müller et al [63] reported that ad libitum meal intake and self-reported EI did not change 4-36 hours after one hour of continuous (~70% peak maximal aerobic capacity) or intermittent walking (intervals of 3 minutes slow [~55% of peak maximal aerobic capacity] & 3 minutes fast walking [~90% of peak maximal aerobic capacity]) in 13 individuals with T2D. Interestingly, it has been reported that individuals with overweight and T2D (n=8) displayed reduced post-prandial fullness in response to a 75-g oral glucose load as compared to those without T2D (n=7) [37].…”
Section: The Impact Of Exercise On Appetite In Individuals With Diabetesmentioning
confidence: 99%
“…In humans, recent evidence suggests that exercises above 75% of maximum oxygen consumption (VO 2 max) can suppress hunger by regulating appetite hormones, a phenomenon known as "exercise-induced anorexia," which may restrict energy intake 6 . Thus, exercise intensity appears to be an important determinant of appetite regulation in humans 7 . In a meta-analysis, Horner et al 8 investigated the effect of acute exercise on gastric emptying and reported controversial results, because the training protocols analyzed were mostly aerobic.…”
Section: Introductionmentioning
confidence: 99%